Short‐term repeatability of the peguero‐lo presti electrocardiographic left ventricular hypertrophy criteria - Dominique Drager; Elsayed Z. Soliman; Michelle L. Meyer; Zhu‐Ming Zhang; Alvaro Alonso; Gerardo Heiss; Eric A. Whitsel (Annals of Noninvasive Electrocardiology, 2021)
Abstract Background Electrocardiographic left ventricular hypertrophy (ECG‐LVH) represents preclinical cardiovascular disease and predicts cardiovascular disease morbidity and mortality. While the newly developed Peguero‐Lo Presti ECG‐LVH criteria have greater sensitivity for LVH than the Cornell voltage and Sokolow–Lyon criteria, its short‐term repeatability is unknown. Therefore, we characterized the short‐term repeatability of Peguero‐Lo Presti ECG‐LVH criteria and evaluate its agreement with Cornell voltage and Sokolow–Lyon ECG‐LVH criteria. Methods Participants underwent two resting, standard, 12‐lead ECGs at each of two visits one week apart (n = 63). We defined a Peguero‐Lo Presti index as a sum of the deepest S wave amplitude in any single lead and lead V4 (i.e., SD + SV4) and defined Peguero‐Lo Presti LVH index as ≥ 2,300 µV among women and ≥ 2,800 µV among men. We estimated repeatability as an intraclass correlation coefficient (ICC), agreement as a prevalence‐adjusted bias‐adjusted kappa coefficient (κ), and precision using 95% confidence intervals (CIs). Results The Peguero‐Lo Presti index was repeatable: ICC (95% CI) = 0.94 (0.91–0.97). Within‐visit agreement of Peguero‐Lo Presti LVH was high at the first and second visits: κ (95% CI) = 0.97 (0.91–1.00) and 1.00 (1.00–1.00). Between‐visit agreement of the first and second measurements at each visit was comparable: κ (95% CI) = 0.90 (0.80–1.00) and 0.93 (0.85–1.00). Agreement of Peguero‐Lo Presti and Cornell or Sokolow–Lyon LVH on any one of the four ECGs was slightly lower: κ (95% CI) = 0.71 (0.54–0.89). Conclusion The Peguero‐Lo Presti index and LVH have excellent repeatability and agreement, which support their use in clinical and epidemiological studies.